Cost-Effectiveness of the U.S. Federal Restaurant Menu Calorie Labeling Law for Improving Diet and Health: A Microsimulation Modeling Study (P22-014-19). (13th June 2019) - Liu, Junxiu; Mozaffarian, Dariush; Lee, Yujin; Sy, Stephen; Abrahams-Gessel, Shafika; Wilde, Parke; Gaziano, Thomas; Micha, Renata
Abstract: Objectives: Excess caloric intake is linked to weight gain, obesity and related diseases including type 2 diabetes and cardiovascular disease (CVD). Obesity incidence has been on the rise, with almost 2 of 3 people being overweight or obese in the US. In 2018, the US federal government passed a law mandating the labeling of calories on all menu items across chain restaurants, as a strategy to support informed consumer choice and reduce caloric intake. Yet, potential health and economic impacts of this policy remain unclear. Methods: We used a validated microsimulation model (CVD-PREDICT) to estimate reductions in CVD events, diabetes cases, gains in quality-adjusted life-years (QALYs), costs, and cost-effectiveness of two policy scenarios: (1) implementation of the federal menu calorie labelling ( menu calorie label ), and (2) further accounting for corresponding industry reformulation ( menu calorie label + reformulation ). The model utilized nationally representative demographic and dietary data from NHANES 2009–2016; policy effects on consumer intake and BMI-disease effects from published meta-analyses; and policy effects on industry reformulation, policy costs (policy administration, industry compliance and reformulation) and health-related costs (formal and informal healthcare costs, productivity costs) from established sources. We conservatively modeled change in calories to change in weight using an established dynamic weight-change model. Findings were evaluated over 10 years and lifetime from a healthcare and societal perspective. Costs were inflated to constant 2018 USD, and costs and QALYs were discounted at 3% annually. We performed probabilistic analyses and a range of one-way sensitivity and subgroup analyses to assess the robustness of our findings. Results: Sample statistics were shown (Table). American adults (35+) consume ∼21% calorie from restaurants (Figure) that would be reduced by 2% due to this law at the population level. Government administration costs were estimated at 11.6$M, industry compliance costs at 652$M, and industry reformulation costs at 9.2$B. Findings for all other analyses will be presented at the meeting. Conclusions: These findings will provide much needed evidence on the health and economic impacts of the US menu calorie labeling law. Funding Sources: NIH, AHA. Supporting Tables, Images and/or Graphs: